The ground reaction force pattern during walking under vestibular-demanding task with/without mastoid vibration: implication for future sensorimotor training in astronauts - Wang, Zhuo; Xie, Haoyu; Chien, Jung Hung (Frontiers in Physiology, 2024)
BackgroundThe Sensory Organization Test condition 5 (SOT5) assesses an astronaut’s vestibular function pre-/post-spaceflight but has a ceiling effect and mainly evaluates standing balance, neglecting the challenges of walking during space missions. A Locomotor Sensory Organization Test (LSOT) has been developed, mirroring the SOT concept but tailored to assess vestibular function during walking. This study aims to advance current knowledge by examining changes in ground reaction force (GRF) during normal walking (LSOT1) and walking in LSOT5 (vision blocked and treadmill speed varied), both with and without mastoid vibrations.MethodsSixty healthy adults were recruited and divided into two groups: one with mastoid vibration and one without. GRF peaks and respective variabilities were analyzed in the vertical (V), anterior-posterior (AP), and medial-lateral (ML) directions during stance cycles. The effects of LSOTs and mastoid vibration on each dependent variable were assessed using Friedman’s two-way analysis of variance by ranks.ResultsThe findings revealed that:1) Walking in LSOT5 increased the variabilities of GRFs regardless of the administration of mastoid vibration; 2) the application of mastoid vibration reduced the amplitude of GRF peaks; and 3) walking in LSOT5 while receiving mastoid vibration was the most challenging task compared to all other tasks in this study.ConclusionThe results indicated that analyzing GRF can detect changes in the strategy of balance control across different sensory-conflicted conditions. The findings could be beneficial for assessing the vestibular function pre- and post-space missions and planning for future sensorimotor training programs aimed at enhancing astronauts’ abilities to navigate unpredictable sensory-conflicted conditions.